PENETAPAN KADAR Co.TRIMOKSAZOL YANG DILAKUKAN DENGAN MENGGUNAKAN SPEKTROFOTOMETER ULTRAVIOLET SECARA SIMULTAN.KLT - Jatmiko Susilo (JURNAL LITBANG, 2006)
Abstract Background* Co-trimoxazol is an combined antibiotics consist of Sulphametoxazol and Trimetoprim (5:1). This substance is related with tetrahydropholic acid synthesis in bacteria to produce imidine and purine. The maximum wavelength of Sulphamethoxazol at 255-257 and Trimetoprim : 287 t 2 nm may be used for concentration assay and the different of polarity properties of these substances may be separated by thin layer chromatography. Objectives : The objective of this research is comparing two methods, UV Spectrophotometry by Simultaneously and by TLC. Method : The research's methodology is experimental laboratory that comparing it's recovery weight of each substance by simultaneously - TLC method. Statistically, Analysis of variants - test and t-test are used to compare between it's standard deviations and means. Results : Sulphamethoxazol and Trimetoprim in Ethanol 95%-NaOH 0,1N (1:3) is show peak absorption at 257 and 289 nm wavelength. Recovery of Sulphamethoxazol is (98.20 + 0.40) Yo and Trimetoprim : (93.69 + 0.75) %. Statistically, the accuracy test, Sulphamethoxazol Fo : 2.325 < F tab (P:0,05, dbf:9,1)=297, andTrimetoprimFo:0.126 <F tab(P:0,05, dbf:1,;7):5.59, andtheprecision test of Sulfametoksazol and Trimetoprim are t cal. : 0.666 < t table (P=0.05; dbt=l0) : 1.81 and tcal. = 0.376 < t tab (P:0,05, dbt: 9) =1.83.. Conclusion : Recovery of Sulphamethoxazol is (98.20 +0.40) % and Trimetoprim (98.69 + 0.75) o/o. The precicion and accuration of these methods are not significantly different, Simultaneously more efficient than TLC. Keywords : Co-Trimo xazol, UV Spectrophotometry Simultaneously-TlC